The identification of resilience in, and the development of a corresponding intervention programme for families with a parent living with major depressive disorder - Bester, Carin (Stellenbosch : University of Stellenbosch, 2009)
Thesis (DPhil (Psychology))--University of Stellenbosch, 2009.